Pengaruh Kualitas Pelayanan Terhadap Loyalitas Anggota dengan Kepuasan Anggota Sebagai Variabel Intervening - Andriani, Ni Wayan Tia; Suartina, I Wayan; Aryana Mahayasa, I Gede (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Intense competition in the banking and financial sector causes savings and loan cooperatives to maintain member loyalty for the sake of the organization's sustainability. Even though advances in technology and information are increasingly driving the banking sector, the culture of mutual cooperation which is the spirit of cooperatives is one of the reasons for the importance of the existence of cooperatives. However, the problem of member loyalty is one of the obstacles to the development of cooperatives in Indonesia in general. This study aims to examine empirically the effect of service quality on member loyalty with satisfaction as an intervening variable. This research was conducted at KSP Eagle Sedana Amertha with a population of 159 members. The number of samples used is 114 members. Data collection was carried out by distributing questionnaires, then the data analysis used was multiple linear regression analysis. This study shows that service quality has a positive effect on member loyalty and satisfaction. Member satisfaction has a positive effect on member loyalty, as well as being able to mediate. This research provides a unique contribution to the theory of reasoned action, namely the relationship between service quality and member satisfaction which can encourage the emergence of member loyalty, especially in the cooperation sector.